Defoliation constrains xylem and phloem functionality. (17th May 2019) - Hillabrand, Rachel M; Hacke, Uwe G; Lieffers, Victor J
Abstract: Insect defoliation contributes to tree mortality under drought conditions. Defoliation-induced alterations to the vascular transport structure may increase tree vulnerability to drought; however, this has been rarely studied. To evaluate the response of tree vascular function following defoliation, 2-year-old balsam poplar were manually defoliated, and both physiological and anatomical measurements were made after allowing for re-foliation. Hydraulic conductivity measurements showed that defoliated trees had both increased vulnerability to embolism and decreased water transport efficiency, likely due to misshapen xylem vessels. Anatomical measurements revealed novel insights into defoliation-induced alterations to the phloem. Phloem sieve tube diameter was reduced in the stems of defoliated trees, suggesting reduced transport capability. In addition, phloem fibers were absent, or reduced in number, in stems, shoot tips and petioles of new leaves, potentially reducing the stability of the vascular tissue. Results from this study suggest that the defoliation leads to trees with increased risk for vascular dysfunction and drought-induced mortality through alterations in the vascular structure, and highlights a route through which carbon limitation can influence hydraulic dysfunction.